Fan Conflicts and State Power in China: Internalised Heteronormativity, Censorship Sensibilities, and Fandom Police. Issue 2 (3rd April 2023) - Wang, Erika Ningxin; Ge, Liang
ABSTRACT: Fans as consumers of cultural products have received a great deal of attention from sociologists and cultural studies academics in recent years, and research on the relationship between fans and state power is gradually gaining traction. Through a 12-month digital ethnography of a large-scale fan conflict surrounding The Untamed, a popular 'Boys' Love'-adapted drama in China, we uncover a complex picture of two-way exploitation between fans and state power. By doing so, the article challenges previous assumptions by Chinese and Western scholars that fan culture is resistant to or negotiates with mainstream culture. We show that by perpetuating heteronormativity and censorship, fans internalise 'reporting' as a norm of legitimacy in consumer culture. Some fans portray themselves as 'fandom police' and use censorship to report 'illegal' comments by their rivals in order to prevail in fan conflicts. However, the power gained by these fandom police is illusory. Their practices are exploited by the state as a tool for censoring media users' speech and cultural production, with the ultimate consequence of perpetuating censorship and heteronormativity.